Combined use of ISCR and biostimulation techniques in incomplete processes of reductive dehalogenation of chlorinated solvents - Herrero, Jofre; Puigserver, Diana; Nijenhuis, Ivonne; Kuntze, Kevin; Carmona, José M. (The Science of the total environment, 2019)
Pools of chloroethenes are more recalcitrant in the transition zone between aquifers and basal aquitards than those elsewhere in the aquifer. Although biodegradation of chloroethenes occur in this zone, it is a slow process and a remediation strategy is needed. The aim of this study was to demonstrate that combined strategy of biostimulation and in situ chemical reduction (ISCR) is more efficient than the two separated strategies. Four different microcosm experiments with sediment and groundwater of a selected field site where an aged perchloroethene (PCE)-pool exists at the bottom of a transition zone, were designed under i) natural conditions, ii) biostimulation with lactic acid, iii) in situ chemical reduction (ISCR) with zero valent iron (ZVI) and under iv) a combined strategy with lactic acid and ZVI. Biotic and abiotic dehalogenation, terminal electron acceptor processes and evolution of microbial communities were investigated for each experiment. The main results where: i) limited reductive dehalogenation of PCE occurs under sulfate-reducing conditions; ii) biostimulation with lactic acid promotes a more pronounced reductive dehalogenation of PCE in comparison under natural conditions, but resulted in an accumulation of cis-dichloroethene (cDCE); iii) ISCR with zero-valent iron (ZVI) facilitates a sustained dehalogenation of PCE and its metabolites to non-halogenated products, however, the iv) combined strategy results in the fastest and sustained dehalogenation of PCE to non-halogenated products in comparison of all four set-ups. These findings suggest that biostimulation and ISCR with ZVI are the most suitable strategy for a complete reductive dehalogenation of PCE-pools in the transition zone. [Display omitted] •Reductive dehalogenation of perchloroethene occurs at sulfate-reducing conditions.•Biostimulation leads to a fast dehalogenation of PCE and accumulation of cDCE.•Desulfovibrio putealis reductively dehalogenates PCE at high concentrations.•Zero value iron is more effective under biotic conditions.•Combined strategy is more efficient than biostimulation and chemical reduction separated.